2019
DOI: 10.1021/acs.chemmater.9b01987
|View full text |Cite
|
Sign up to set email alerts
|

Redox Paradox of Vanadium in Tavorite LiVPO4F1–yOy

Abstract: Vanadyl-type defects in vanadium oxy-fluoride phosphates confer interesting properties to these materials as positive electrodes in Li-ion or Na-ion batteries. The influence of defects concentration on the phase diagram and redox mechanisms in LiVPO4F1-yOy Tavorite phases has been investigated by combining operando Synchrotron X-ray powder diffraction (SXRPD) and X-ray absorption spectroscopy (XAS). Operando X-ray absorption near edge structure (XANES) reveals the activation of the V 4+ =O/V 5+ =O redox couple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…It was demonstrated that in many fluoride phosphates the fluorine-to-oxygen ratio plays a significant role in governing the electrochemical performance, which was observed and thoroughly studied for many vanadium-containing fluoride phosphates. However, the influence of the F:O ratio on the electrochemical parameters is vastly complicated because both V 3+ /V 4+ and V 4+ /V 5+ (or [V=O] 2+ /[V=O] 3+ ) redox transitions are typically electrochemically active 54 . Deviation from the stoichiometric F:O ratio thus results in changing of the electrochemical parameters (operating potential, de/intercalation mechanism, C-rates, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that in many fluoride phosphates the fluorine-to-oxygen ratio plays a significant role in governing the electrochemical performance, which was observed and thoroughly studied for many vanadium-containing fluoride phosphates. However, the influence of the F:O ratio on the electrochemical parameters is vastly complicated because both V 3+ /V 4+ and V 4+ /V 5+ (or [V=O] 2+ /[V=O] 3+ ) redox transitions are typically electrochemically active 54 . Deviation from the stoichiometric F:O ratio thus results in changing of the electrochemical parameters (operating potential, de/intercalation mechanism, C-rates, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…This strategy aimed at decreasing the difference in voltage between Li insertion and extraction reactions, conferring to the material a high energy density (i.e., 820 Wh/kg) in a reduced voltage range (i.e., 2.0–4.5 V vs. Li + /Li) with the activation of the V 3+ /V 4+ and V 4+ /V 5+ redox couples, respectively. Further investigation of the LiVPO 4 F-LiVPO 4 O tie-line has allowed several compositions to stabilize in which the competition between ionicity of the V 3+ -F bond and covalency of the V 4+ =O bond distorts the structure, freezes the framework upon Li extraction and hence allows for improved rate capabilities compared with the end-member phases [ 80 , 81 ]. Interestingly, upon Li deintercalation from these materials, the V 4+ =O/V 5+ =O redox couple is triggered first before the V 3+ /V 4+ is activated in fluorine rich environments leading to the formation of a mixed valence V 3+ -V 5+ phase at half charge [ 81 ].…”
Section: Low Voltage Multi-electron Reactions In Tavorites LI mentioning
confidence: 99%
“…Further investigation of the LiVPO 4 F-LiVPO 4 O tie-line has allowed several compositions to stabilize in which the competition between ionicity of the V 3+ -F bond and covalency of the V 4+ =O bond distorts the structure, freezes the framework upon Li extraction and hence allows for improved rate capabilities compared with the end-member phases [ 80 , 81 ]. Interestingly, upon Li deintercalation from these materials, the V 4+ =O/V 5+ =O redox couple is triggered first before the V 3+ /V 4+ is activated in fluorine rich environments leading to the formation of a mixed valence V 3+ -V 5+ phase at half charge [ 81 ]. Although surprising, this redox mechanism is in full agreement with the operating voltage of the end-member phases, the V 4+ /V 5+ redox couple being activated at 3.95 V in LiVPO 4 O and the V 3+ /V 4+ redox couple at 4.25 V in LiVPO 4 F due to the absence of vanadyl distortion in LiVPO 4 F and VPO 4 F.…”
Section: Low Voltage Multi-electron Reactions In Tavorites LI mentioning
confidence: 99%
“…The O/F clustering tendency observed here is in good agreement with the observation of microstrains and deviations from the Vegard's law for the solid solution LiVPO 4 F 1‐y O y reported in our previous study. The present study is a first step to better understand the complex redox behavior observed for the LiVPO 4 F 1‐y O y materials in Li cells with the activation of the V IV O/V V O redox couple during the first step of the charge, and then upon further Li + extraction, the activation of the V 3+ /V 4+ redox couple in fluorine‐rich environments [ 9 ] that may result from the complex electronic structure and clustering tendency observed.…”
Section: Resultsmentioning
confidence: 99%
“…[8] The concentration of vanadyl-type defects was shown to have a strong influence on the electrochemical behavior in terms of redox processes involved, energy density, cyclability, and rate capability. [8,9] A better understanding of the local structural arrangement is of prime importance for further material optimization.…”
mentioning
confidence: 99%